gou000096: Ramassage de pommes de terre - Deltour, Louis
"copyright: Deltour André, Deltour Phillippe Forces Murales, voorstudie. Origineel in Institut Belge in Londen (330cm x 140 cm). FULL TEXT AVAILABLE AT AMSAB-ISH"